Performance of concrete containing coconut shell as coarse aggregates - Adnan, Suraya Hani; Muhamad, Nurul Naimah; Mohd Yassin, Nurain Izzati (Penerbit UTHM, 2017)
In civil engineering, concrete is a most composite material widely used in construction work (Alwi, 2009). Concrete is a material produced from several materials such as cement, coarse and fine aggregates, and water mixture. These materials are supplemented by specific mixing rate as established for obtaining the desired criteria. Highly demand for the use of concrete as a building material due to several factors, which is material for the production of concrete is easily available and cheap (Dina, 2006). In addition, concrete is a material with the highly strength compared to other building materials. Based on Ramachandrudu (2012), coconut shell was used as an aggregates replacement in the manufacture of lightweight concrete. The selection of coconut shell as lightweight concrete material is one of the efforts to reduce pollution resulting from the disposal of solid waste material. According to the article (“Coconut in India,” 2011), coconut grown in over 86 countries worldwide and generates more than 54 billion nuts per annum (Yerramala, 2012). With the use of coconut shell as a replacement material in the construction industry, indirectly reduce the costs production of concrete and the disposal of waste (Gunasekaran et al., 2012). Coconut shells have been used in the manufacturing of lightweight concrete, indirectly creating new inventions that could be studied more in the future in order to improve the concrete manufacturing industry as well as save costs and reduce solid waste disposal. Therefore, this research is conducted to identify the potential use of coconut shell as an aggregates replacement in concrete mixture.